Relative humidity requirements and incubation periods for the Colletotrichum gloeosporioides conidia infection in papaya fruit. - Durán, Alfredo; Ramírez, Lenín; Mora, Dennis (Agronomía Mesoamericana, 2016)
The research was carried out at the University of Costa Rica's phytopathology laboratory between October 1995 and March 1996. In an initial phase, some creole papaya fruits from Gu.cimo (Limón province) were used. In order to eliminate latent infections, they were washed and immersed in hot water (49° C for 20 minutes). The fruits were then randomly placed in groups of 20, which conformed each treatment. Finally, they were inoculated by spraying with 5.5 ml of a 10.000 Colletotrichum gloeosporioides spores per mililiter suspension; then they were placed in plastic boxes and stored in containers with a 30°C temperature and relative humidities of 70%, 80%, and 90%. Fruits were kept in the compartments for periods of 5, l0, 15, 20 and 25 hours. Temperature and relative humidity were monitored during the experiment through the incubator's sensors and with a portable hydrothermograph. Finally, the incidence and severity of anthracnose was evaluated. During the second phase, fruits of the Hawaiian sunrise variety were used, following the same procedures applied to the native fruits. In native fruits, 100% of those placed at 80% and 90% relative humidity were contaminated after being in the compartment for five hours. The incidence decreased in the group with 70% relative humidity. The damage level increased with increases in relative humidity, although some erratic behavior was observed. In the test with Hawaiian fruit, the disease incidence increased according with incubation time. Severity showed a similar behavour; however, there was also erratic behavour here.